Scope and Limitations of a Direct Arylation Polycondensation Scheme in the Synthesis of PCPDTBT‐Type Copolymers. Issue 11 (4th December 2014) - Kowalski, Sebastian; Allard, Sybille; Scherf, Ullrich; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> Direct arylation polycondensation represents a promising alternative to the currently used aryl–aryl coupling schemes for conjugated polymer synthesis that is characterized by a potentially lower impact on the environment and reduced costs. However, scope and limitations of this novel protocol are not fully understood until now. Two main aspects are, hereby, i) the chemical nature of side reactions that occur during coupling of nonactivated and dihalogenated aromatic monomers, and ii) the influence of steric and electronic factors on the reactivity of the monomers. Within this communication, the 4, 4‐bis(2‐ethylhexyl)‐cyclopenta[1, 2‐b:5, 4‐b′]dithiophene (CPDT)/2, 1, 3‐benzothiadiazole (BT) monomer couple for direct arylation synthesis of the alternating copolymer poly(4, 4‐(2‐ethylhexyl)‐cyclopenta[2, 1‐b:3, 4‐b′]dithiophene‐alt‐2, 1, 3‐benzothiadiazole) (PCPDTBT) is studied and homocoupling identified as the dominating side reaction. The study demonstrates that homocoupling can be almost completely suppressed through a clever choice of the reaction conditions. Finally, the findings implicate that mainly electronic factors control the reactivity of both monomers.